Transumbilical single-incision laparoscopic hysterectomy with conventional laparoscopic instruments in patients with symptomatic leiomyoma and/or adenomyosis - Chailert Phongnarisorn (2018)
Purpose To evaluate the feasibility, safety and perioperative outcome of single-incision laparoscopic hysterectomy (SILH) using conventional laparoscopic instruments for treatment of patients with symptomatic leiomyoma and/or adenomyosis. Methods A retrospective study (Canadian Task Force ClassiWcation II-2) was carried out at a tertiary referral university hospital from August 2009 to January 2010. Women diagnosed with leiomyoma/adenomyosis and scheduled to undergo SILH were enrolled. The criteria included uterine size ≤16 weeks' gestation on pelvic examination, no suspected malignancy on sonography, normal cytology and contraindications for vaginal hysterectomy. The medical records of all consecutive patients undergoing SILH were reviewed. The main outcome measurements were the feasibility and safety of SILH in terms of conversion rate, body mass index (BMI), uterine weight, operative time, estimated blood loss, drop in hemoglobin level and complications. Results Eleven consecutive patients diagnosed with leiomyoma (10) and adenomyosis (1) underwent SILH successfully during the study period, without conversion or requirement of any extra port. The mean age and BMI of the patients were 47.4 ± 4.27 years and 25.2 ± 4.61 kg/m 2, respectively. The average clinical uterine size and uterine weight were 13.2 ± 2.48 weeks' gestation and 281.6 ± 152.89 g, respectively. The mean operative time was 163.3 ± 20.46 min. The mean estimated blood loss and drop in hemoglobin level were 114.5 ± 48.65 ml and 0.33 ± 0.62 g/dl, respectively. No intra-operative complication occurred. Postoperative febrile morbidity was found in two patients. The follow-up at 14 days and 6 weeks postoperatively was uneventful. Conclusions SILH using conventional laparoscopic instrumentation might be a feasible and safe alternative to standard multiple incision laparoscopic hysterectomy in selected patients with symptomatic benign uterine tumor. The potential advantages of our technique are: it is simple and cost-eVective, due to the use of conventional, userfriendly laparoscopic instruments. Additional studies on SILH are needed to demonstrate its safety, deWne selective criteria and determine any beneWts over conventional laparoscopic hysterectomy. © Springer-Verlag 2010.